2021
DOI: 10.3390/socsci10050160
|View full text |Cite
|
Sign up to set email alerts
|

Are Mothers and Daughters Most Important? How Gender, Childhood Family Dissolution and Parents’ Current Living Arrangements Affect the Personal Care of Parents

Abstract: This study examines adult children’s propensity to provide personal care to older mothers and fathers. The theory of intergenerational solidarity facilitates the understanding of commitment and support between adult children and parents. Solidarity may depend on childhood events as well as the current situation, and we therefore focus on whether there was a parental breakup in childhood and the parent’s current living arrangements. We also focus on the gendered aspects of the relations as earlier research has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…In the Swedish context, results provide a more nuanced picture of gender differences in intergenerational old age care. This study highlights the importance of assessing care intensity and type of care provided (Szebehely et al 2014 ; von Essen and Svedberg 2020 ) in combination with accounting for the dyad characteristics, specifically geographic proximity (Jegermalm 2006 ; Kridahl and Duvander 2021 ) for better understanding potential gender differences. The non-differential social class patterns mirror previous research that has not found differences in educational background in caregiving by adult children in Sweden (Sarasa Urdiola and Billingsley 2008 ; von Essen and Svedberg 2020 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the Swedish context, results provide a more nuanced picture of gender differences in intergenerational old age care. This study highlights the importance of assessing care intensity and type of care provided (Szebehely et al 2014 ; von Essen and Svedberg 2020 ) in combination with accounting for the dyad characteristics, specifically geographic proximity (Jegermalm 2006 ; Kridahl and Duvander 2021 ) for better understanding potential gender differences. The non-differential social class patterns mirror previous research that has not found differences in educational background in caregiving by adult children in Sweden (Sarasa Urdiola and Billingsley 2008 ; von Essen and Svedberg 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…Gender differences tend to be insignificant when considering whether care has been provided at all, or at least monthly (Szebehely et al 2014 ; von Essen and Svedberg 2020 ). However, there are gender differences regarding the type of care and care intensity; daughters are more likely to provide intensive care, for example, personal care (Kridahl and Duvander 2021 ) together with other care tasks. Sons, on the other hand, tend to provide practical care (Jegermalm 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…These gendered parental norms are also reflected in stepfamilies, with breadwinning constituting a large part of a father's identity, leading stepfathers to spend more on their stepchildren's expenses than stepmothers (Hans & Coleman, 2009). Moreover, women have been argued to have “kin‐keeping roles” in (step)families suggesting that women facilitate better father–child relationships (Kridahl & Duvander, 2021). Biological mothers might therefore encourage their partners (i.e., stepfathers) to contribute more than biological fathers might do so with their partners (i.e., stepmothers).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…These gendered parental norms are also reflected in stepfamilies, with breadwinning constituting a large part of a father's identity, leading stepfathers to spend more on their stepchildren's expenses than stepmothers (Hans & Coleman, 2009). Moreover, women have been argued to have "kin-keeping roles" in (step) families suggesting that women facilitate better father-child relationships (Kridahl & Duvander, 2021). Biological mothers might therefore encourage their partners (i.e., stepfathers) to contribute more than biological fathers might do so with their partners (i.e., stepmothers…”
Section: Gender Of Stepparentsmentioning
confidence: 99%